2015
DOI: 10.1108/jhtt-01-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the homestay experience and brand equity

Abstract: Purpose – The purpose of this paper is to investigate the correlation between customer experience and brand equity for a homestay establishment in Eastern Taiwan. Design/methodology/approach – Visitors staying at Yuehetang Rural Residence (YRR) during the month of January 2013 were surveyed, and the data were analyzed using descriptive statistics, reliability analysis and typical correlation. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…The search for the real purpose for business and develop a business model with a social goal is shown to be essential to achieve the above [10,87], without forgetting the stakeholder view [88], and that profits are not the only thing necessary to create value [89], be coherent with the corporate purpose [13]. In addition, it is shown that when looking after the environment is good for profit [90], and to get the loyalty of customers [60,91]. The economic and environmental aspects cannot be differentiated [92,93]; it is an intangible experience which consumers perceive [94].…”
Section: Case Studies' Analysismentioning
confidence: 99%
“…The search for the real purpose for business and develop a business model with a social goal is shown to be essential to achieve the above [10,87], without forgetting the stakeholder view [88], and that profits are not the only thing necessary to create value [89], be coherent with the corporate purpose [13]. In addition, it is shown that when looking after the environment is good for profit [90], and to get the loyalty of customers [60,91]. The economic and environmental aspects cannot be differentiated [92,93]; it is an intangible experience which consumers perceive [94].…”
Section: Case Studies' Analysismentioning
confidence: 99%
“…Banyak penelitian telah membahas berbagai aspek dan manfaat dari ekuitas merek berbasis pelanggan seperti yang dilakukan [22] yang melakukan penelitian pada bidang farmasi dan kesehatan. [17] mengemukakan bahwa pada industri hospitality dan tourism technology ekuitas merek berbasis pelanggan masih menjadi sorotan untuk sebuah penelitian. [21] melakukan penelitian ekuitas merek berbasis pelanggan pada industri perbankan.…”
Section: Iunclassified
“…,CR CI/RI (6) In this formula, (CR is random consistency proportion; CI and RI is the consistency index and the average random consistency index). CR<0.1, judgement matrix is in line with consistency.…”
Section: CImentioning
confidence: 99%